BOOK REVIEWS (Journal of Finance, 1954)
Book reviewed in this article: The Volume of Corporate Bond Financing since 1900 . By W. B raddock H ickman Case Problems in Finance . By P earson H unt and C harles M. W illiams Business Organization and Combination . By R ichard N orman O wens Financial Management for the Small Businessman . By L. A. T ungate . The Role of the Sales Finance Companies in the American Economy . By C lyde W illiam P helps Investment of Life Insurance Funds . Edited by D avid M c C ahan Die Systeme der Exportrisikogarantie in Deutschland, Grossbritannien, Belgien, Frankreich, den Niederlanden, der Schweiz und Schweden . By W erner L ichey The Taxation of Corporate Surplus Accumulations . By J ames K. H all International Monetary Co‐operation 1945–52 . By B rian T ew . Money, Debt, and Economic Activity . By A lbert G ailord H art State Supervision of Municipal Finance . By T. E. M c M illan , J r Taxation and Incentive . By L ady R hys ‐W illiams The Limits of Taxable Capacity: A Symposium . By the T ax I nstitute